Identification of the terebrantian thrips (Insecta, Thysanoptera) associated with cultivated plants in Java, Indonesia - Sartiami, Dewi (Pensoft Publishers, 2013)
Abstract. An illustrated identification key is provided to 49 species of Thysanoptera, Terebrantia that have been found in association with cultivated plants in Java. This is the first published identification system to this group of insects from Indonesia, and includes 15 species not previously recorded from Indonesia, and a further three species not previously recorded from Java. A table is provided indicating the plants from which thrips were taken.